A atuação do núcleo de enfrentamento ao tráfico de pessoas NETP/SEJUSC/AM frente ao problema do tráfico de pessoas no estado do Amazonas no biênio 2012/2013 - Santos, Priscila Teixeira Da Costa (2016)
The general objective of this thesis was to analyze, from a qualitative perspective, the Amazon state action in the confrontation crime of human trafficking. For this, the following specific objectives were established: the present state of the human trafficking crime in the State of Amazonas; profile the victims who have records in NETP/SEJUSC the biennium 2012/2013; scale and state action to combat and prevent the trafficking in persons crime. As for the methodology, the work is characterized as a documentary research of qualitative and quantitative character that was based on official documentary records for the period 2012-2013 the Center for Combating Trafficking in Persons of the Secretary of State for Justice and Human Rights - NETP, located in Manaus, with the main purpose of examining, from a qualitative perspective, the Amazon state action in the confrontation crime of human trafficking. It is necessary to further clarify that, although present in this study quantitative data for the approach to the subject, it does not qualify as a statistical research. To complement the survey also was held an interview with the Head of Promotion and Advocacy - DPDD the Secretary of State for Justice, Human Rights and Citizenship - SEJUSC, which already operates since 2010 in this role, at the Center to Combat Trafficking in Persons - NETP, that is, from when the core was officially deployed. Among the key findings related to the victims of the profile include the following: there is a incidence of victims classified as minor, under 18 years, about 78.58% in 2012 and 15.39% in 2013. As for gender, both in 2012 (85.71%) as in 2013 (80.77%), there was a prevalence of females. As for nationality, in 2012, 92.85% of the cases were of Brazilian and 7.15% of foreigners. As early as 2013, the nationality of cases was 100% of Brazilians. During the research, it was realized that the data recorded by the NETP/SEJUSC/AM still have flaws in their records, as the absence of important data and do not appear complete information to characterize the profile of the victim. In conclusion it can be noted that, despite some flaws, the State of Amazonas has performed important role in combating criminal form of trafficking in persons through actions and NETP programs/ SEJUSC/AM.